Persistence and Exposure Assessment of Insecticide Indoxacarb Residues in Vegetables - Patra, Sandip; Das, Anupam; Rakshit, Rajiv; Choudhury, Suborna Roy; Roy, Shyamashree; Mondal, Tilak; Samanta, Arunava; Ganguly, Pritam; Alsuhaibani, Amnah Mohammed; Gaber, Ahmed; Brestic, Marian; Skalicky, Milan; et al. (Frontiers in Nutrition, 2022)
Indoxacarb, a promising new generation insecticide, is gaining popularity among vegetable growers in West Bengal, India, for controlling a large number of insects. However, it may simultaneously also increase the risk of contamination in the edible portions of the vegetables. This study was planned to analyze the persistence behavior of indoxacarb in cabbages, tomatoes, and soil. Moreover, indoxacarb residue contents were estimated to assess both the dietary and soil ecological risks associated with the application of the same. The experimental location was important because West Bengal is the leading vegetables producing state in India. Indoxacarb was found to dissipate quickly with a half-life ranging between 1.55 and 2.76 days, irrespective of the vegetable, dose, and season, and the safe waiting period was very less. The findings indicate that both vegetables can be safely consumed 1 day after the final spray. However, the risk to soil algae is predicted to be unacceptably high, which needs to be studied extensively.